PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS IV SD NEGERI 013 PAGARAN TAPAH DARUSSALAM - Kelana ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research is motivated by the lack of ability to read aloud the fourth grade primary school 013 Pagaran Tapah Darussalam. This study aims to improve the ability to read aloud using the method of giving the task to improve the ability to read aloud the fourth grade students of SD Negeri 013 Pagaran Tapah Darussalam. Subjects of this study is the fourth grade students of SD Negeri 013 Pagaran Tapah Darussalam totaled 20 students, consisting of 10 female students and 10 male students in the academic year 2014-2015. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of the research shows that the students' skills in reading aloud increased. It is known from preliminary data the average value of 63.2. When viewed from the classical completeness, there are 19.2% of students (5 persons) who finished obtaining a minimum value of 70 (according to the standard KKM). However, after the implementation of the method of assignment, obtained an average value of 68.9 or completeness of 50% of students (13 people). Then in the second cycle, to reach an average value of 81.4 or completeness of 100%. Thus, this study is said to been able to.